Alterations in the helicoverpa armigera midgut digestive physiology after ingestion of pigeon pea inducible leucine aminopeptidase - Lomate, Purushottam R.; Jadhav, Bhakti R.; Giri, Ashok P.; Hivrale, Vandana K. (Plos One, 2013)
Jasmonate inducible plant leucine aminopeptidase (LAP) is proposed to serve as direct defense in the insect midgut. However, exact functions of inducible plant LAPs in the insect midgut remain to be estimated. In the present investigation, we report the direct defensive role of pigeon pea inducible LAP in the midgut of Helicoverpa armigera (Lepidoptera: Noctuidae) and responses of midgut soluble aminopeptidases and serine proteinases upon LAP ingestion. Larval growth and survival was significantly reduced on the diets supplemented with pigeon pea LAP. Aminopeptidase activities in larvae remain unaltered in presence or absence of inducible LAP in the diet. On the contrary, serine proteinase activities were significantly decreased in the larvae reared on pigeon pea LAP containing diet as compared to larvae fed on diet without LAP. Our data suggest that pigeon pea inducible LAP is responsible for the degradation of midgut serine proteinases upon ingestion. Reduction in the aminopeptidase activity with LpNA in the H. armigera larvae was compensated with an induction of aminopeptidase activity with ApNA. Our findings could be helpful to further dissect the roles of plant inducible LAPs in the direct plant defense against herbivory.

Characterization of a chemostable serine alkaline protease from Periplaneta americana - Sanatan, Prashant T.; Lomate, Purushottam R.; Giri, Ashok P.; Hivrale, Vandana K. (BMC Biochemistry, 2013)
Background: Proteases are important enzymes involved in numerous essential physiological processes and hold a strong potential for industrial applications. The proteolytic activity of insects' gut is endowed by many isoforms with diverse properties and specificities. Thus, insect proteases can act as a tool in industrial processes. Results: In the present study, purification and properties of a serine alkaline protease from Periplaneta americana and its potential application as an additive in various bio-formulations are reported. The enzyme was purified near to homogeneity by using acetone precipitation and Sephadex G-100 gel filtration chromatography. Enzyme activity was increased up to 4.2 fold after gel filtration chromatography. The purified enzyme appeared as single protein-band with a molecular mass of similar to 27.8 kDa in SDS-PAGE. The optimum pH and temperature for the proteolytic activity for purified protein were found around pH 8.0 and 60 degrees C respectively. Complete inhibition of the purified enzyme by phenylmethylsulfonyl fluoride confirmed that the protease was of serine-type. The purified enzyme revealed high stability and compatibility towards detergents, oxidizing, reducing, and bleaching agents. In addition, enzyme also showed stability towards organic solvents and commercial detergents. Conclusion: Several important properties of a serine protease from P. Americana were revealed. Moreover, insects can serve as excellent and alternative source of industrially important proteases with unique properties, which can be utilized as additives in detergents, stain removers and other bio-formulations. Properties of the P. americana protease accounted in the present investigation can be exploited further in various industrial processes. As an industrial prospective, identification of enzymes with varying essential properties from different insect species might be good approach and bioresource.
Keywords: Chemostability; Industrial catalyst; Insect proteases; Periplaneta americana; Serine alkaline protease

Compensatory proteolytic responses to dietary proteinase inhibitors from Albizia lebbeck seeds in the helicoverpa armigera larvae - Hivrale, Vandana K.; Lomate, Purushottam R.; Basaiyye, Shriniwas S.; Kalve, Neeta D. (Arthropod-Plant Interactions, 2013)
Plant proteinase inhibitors (PIs) have been shown to reduce the growth rates in larvae of numerous insect species. On the other hand, insects can also regulate their proteinases against plant PIs. In the present study, we report the compensatory activities of Helicoverpa armigera (Hubner) (Lepidoptera: Noctuidae) gut proteinases against the PIs of Albizia lebbeck seeds. Total of ten proteinase inhibitor bands were detected in the seed extract of A. lebbeck. Bioassays were conducted by feeding H. armigera larvae on diet containing partially purified PIs from A. lebbeck seeds. Results show that larval growth and survival was significantly reduced by A. lebbeck PIs. We found that higher activity H. armigera gut proteinase (HGP) isoforms observed in the midgut of control larvae were inhibited in the midgut of larvae fed on test diet. Some HGP isoforms were induced in the larvae fed on PI containing test diet; however, these isoforms showed lower activity in the larvae fed on control diet. Aminopeptidase activities were significantly increased in the midgut of larvae fed on test diet. A population of susceptible and resistant enzymes was observed in the midgut of H. armigera, when fed on diet containing PIs from A. lebbeck seeds. Our initial observations indicate that H. armigera can regulate its digestive proteinase activity against non-host plant PIs, too. It is important to study the exact biochemical and molecular mechanisms underlying this phenomenon in order to develop PI-based insect control strategies.
Keywords: Albizia lebbeck; Helicoverpa armigera; Midgut proteinases; Proteinase inhibitors; regulation

Molecular insights into resistance mechanisms of lepidopteran insect pests against toxicants - Dawkar, Vishal V.; Chikate, Yojana R.; Lomate, Purushottam R.; Dholakia, Bhushan B.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Proteome Research, 2013)
Insect pests remain a major reason for crop loss worldwide despite extensive use of chemical insecticides. More than B 50% of all insecticides are organophosphates, followed by synthetic pyrethroids, organochlorines, carbamates, and biopesticides, and their continued use may have many environmental, agricultural, medical, and socioeconomic issues. Importantly, only a countable number of insects have acquired the status of crop pests, mostly due to monoculture of crop plants and polyphagous nature of the insects. We focus on A adaptations of Lepidopteran insects to phytochemicals and synthetic pesticides in native and modern agricultural systems. Because of heavy use of chemical insecticides, a strong selection pressure is imposed on insect populations, resulting in the emergence of resistance against candidate compound(s). Current knowledge suggests that insects generally implement a three-tier system to overcome the effect of toxic compounds at physiological, biochemical, and genetic levels. Furthermore, we have discussed whether the adaptation to phytochemicals provides an advantage to the insect while encountering synthetic insecticide molecules. Specific metabolic pathways employed by insects to convert deterrents into less toxic forms or their removal from the system are highlighted. Using the proteomics approach, insect proteins interacting with insecticides can be identified, and their modification in resistant insects can be characterized. Also, systems biology studies can offer useful cues to decipher the molecular networks participating in the metabolism of detrimental compounds.
Keywords: field crops; insect-pests; insecticide; Lepidoptera; proteomics; resistance mechanisms

Identification and expression profiling of helicoverpa armigera microRNAs and their possible role in the regulation of digestive protease genes - Lomate, Purushottam R.; Mahajan, Neha S.; Kale, Sandip M.; Gupta, Vidya S.; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2014)
The present investigation is an effort to determine the possible roles of microRNAs (miRNAs) in the regulation of protease gene expression in Helicoverpa armigera upon exposure to plant protease inhibitors (PIs). Using Illumina platform, deep sequencing of 12 small RNA libraries was performed from H. armigera larvae fed on artificial diet (AD) or recombinant Capsicum annuum PI-7 (rCanPI-7) incorporated diet, at various time intervals (0.5, 2, 6, 12, 24, and 48 h). Sequencing data were analyzed with miRDeep2 software; a total of 186 unique miRNAs were identified from all the 12 libraries, out of which 96 were conserved while 90 were novel. These miRNAs showed all the conserved characteristics of insect miRNAs. Homology analysis revealed that most of the identified miRNAs were insect-specific, and more than 50 miRNAs were Lepidoptera-specific. Several candidate miRNAs (conserved and novel) were differentially expressed in rCanPI-7 fed larvae as compared to the larvae fed on AD. H. armigera miRNAs were found to have target sites in several protease genes as well as in protease regulation related genes such as serine PI and immune reactive PI. As expected, negative correlation in the relative abundance miRNAs and their target mRNAs was evident from qualitative real time polymerase chain reaction analysis. The investigation revealed potential roles of miRNAs in H. armigera protease gene regulation. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Deep sequencing; Helicoverpa armigera; miRNAs; Protease gene regulation; Protease inhibitors

Ecological turmoil in evolutionary dynamics of plant-insect interactions: defense to offence - Mishra, Manasi; Lomate, Purushottam R.; Joshi, Rakesh S.; Punekar, Sachin A.; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
Available history manifests contemporary diversity that exists in plant-insect interactions. A radical thinking is necessary for developing strategies that can co-opt natural insect-plant mutualism, ecology and environmental safety for crop protection since current agricultural practices can reduce species richness and evenness. The global environmental changes, such as increased temperature, CO (2) and ozone levels, biological invasions, land-use change and habitat fragmentation together play a significant role in re-shaping the plant-insect multi-trophic interactions. Diverse natural products need to be studied and explored for their biological functions as insect pest control agents. In order to assure the success of an integrated pest management strategy, human activities need to be harmonized to minimize the global climate changes. Plant-insect interaction is one of the most primitive and co-evolved associations, often influenced by surrounding changes. In this review, we account the persistence and evolution of plant-insect interactions, with particular focus on the effect of climate change and human interference on these interactions. Plants and insects have been maintaining their existence through a mutual service-resource relationship while defending themselves. We provide a comprehensive catalog of various defense strategies employed by the plants and/or insects. Furthermore, several important factors such as accelerated diversification, imbalance in the mutualism, and chemical arms race between plants and insects as indirect consequences of human practices are highlighted. Inappropriate implementation of several modern agricultural practices has resulted in (i) endangered mutualisms, (ii) pest status and resistance in insects and (iii) ecological instability. Moreover, altered environmental conditions eventually triggered the resetting of plant-insect interactions. Hence, multitrophic approaches that can harmonize human activities and minimize their interference in native plant-insect interactions are needed to maintain natural balance between the existence of plants and insects.
Keywords: Climatic change; Co-evolution; Ecosystem; Human interference; Plant-insect interaction

Structural features of diverse Pin-II proteinase inhibitor genes from capsicum annuum - Mahajan, Neha S.; Dewangan, Veena; Lomate, Purushottam R.; Joshi, Rakesh S.; Mishra, Manasi; Gupta, Vidya S.; Giri, Ashok P. (Planta, 2015)
The proteinase inhibitor (PI) genes from Capsicum annuum were characterized with respect to their UTR, introns and promoter elements. The occurrence of PIs with circularly permuted domain organization was evident. Several potato inhibitor II (Pin-II) type proteinase inhibitor (PI) genes have been analyzed from Capsicum annuum (L.) with respect to their differential expression during plant defense response. However, complete gene characterization of any of these C. annuum PIs (CanPIs) has not been carried out so far. Complete gene architectures of a previously identified CanPI-7 (Beads-on-string, Type A) and a member of newly isolated Bracelet type B, CanPI-69 are reported in this study. The 5' UTR (untranslated region), 3'UTR, and intronic sequences of both the CanPI genes were obtained. The genomic sequence of CanPI-7 exhibited, exon 1 (49 base pair, bp) and exon 2 (740 bp) interrupted by a 294-bp long type I intron. We noted the occurrence of three multi-domain PIs (CanPI-69, 70, 71) with circularly permuted domain organization. CanPI-69 was found to possess exon 1 (49 bp), exon 2 (551 bp) and a 584-bp long type I intron. The upstream sequence analysis of CanPI-7 and CanPI-69 predicted various transcription factor-binding sites including TATA and CAAT boxes, hormone-responsive elements (ABRELATERD1, DOFCOREZM, ERELEE4), and a defense-responsive element (WRKY71OS). Binding of transcription factors such as zinc finger motif MADS-box and MYB to the promoter regions was confirmed using electrophoretic mobility shift assay followed by mass spectrometric identification. The 3' UTR analysis for 25 CanPI genes revealed unique/distinct 3' UTR sequence for each gene. Structures of three domain CanPIs of type A and B were predicted and further analyzed for their attributes. This investigation of CanPI gene architecture will enable the better understanding of the genetic elements present in CanPIs.
Keywords: CanPI; Capsicum; Gene architecture; Promoter; Proteinase inhibitor

Integrated transcriptomic and proteomic analyses suggest the participation of endogenous protease inhibitors in the regulation of protease gene expression in helicoverpa armigera - Lomate, Purushottam R.; Dewangan, Veena; Mahajan, Neha S.; Kumar, Yashwant; Kulkarni, Abhijeet; Wang, Li; Saxena, Smita; Gupta, Vidya S.; Giri, Ashok P. (Molecular & Cellular Proteomics, 2018)
Insects adapt to plant protease inhibitors (PIs) present in their diet by differentially regulating multiple digestive proteases. However, mechanisms regulating protease gene expression in insects are largely enigmatic. Ingestion of multi-domain recombinant Capsicum annuum protease inhibitor-7 (CanPI-7) arrests growth and development of Helicoverpa armigera (Lepidoptera: Noctuidae). Using de novo RNA sequencing and proteomic analysis, we examined the response of H. armigera larvae fed on recombinant CanPI-7 at different time intervals. Here, we present evidence supporting a dynamic transition in H. armigera protease expression on CanPI-7 feeding with general down-regulation of protease genes at early time points (0.5 to 6 h) and significant up-regulation of specific trypsin, chymotrypsin and aminopeptidase genes at later time points (12 to 48 h). Further, coexpression of H. armigera endogenous PIs with several digestive protease genes were apparent. In addition to the differential expression of endogenous H. armigera PIs, we also observed a distinct novel isoform of endogenous PI in CanPI-7 fed H. armigera larvae. Based on present and earlier studies, we propose potential mechanism of protease regulation in H. armigera and subsequent adaptation strategy to cope with anti-nutritional components of plants.

Plant protease inhibitors induced oxidative and nutritional stress in helicoverpa armigera unveils multifaceted survival strategies: a lipidomic and metabolomic view - Dewangan, Veena; Gupta, Sonu Kumar; Deshpande, Neha; Lomate, Purushottam R.; Kumar, Yashwant; Giri, Ashok P. (ACS Omega, 2026)
Plant protease inhibitors impede insect growth and development by targeting digestive proteases. In response, insects adapt by modulating protease expression; however, their survival may not rely solely on digestive plasticity and likely involves broader physiological adjustments. To investigate this, we performed an integrated lipidomic and metabolomic analysis of Helicoverpa armigera larvae fed on the recombinant Capsicum annuum protease inhibitor (rCanPI-7), a four-domain inhibitor with potent activity against insect trypsins and chymotrypsins. The results revealed extensive metabolic reprogramming in H. armigera under rCanPI-7-induced stress, prominently affecting amino acid, glutathione, and pyrimidine metabolic pathways with distinct shifts in alanine, arginine, histidine, and branched-chain amino acid metabolism. Suppression of glycolysis and the tricarboxylic acid cycle indicated reduced primary energy metabolism, while oxidative stress was evident from glutathione depletion, lipid peroxidation, and ceramide accumulation, which are hallmarks of mitochondrial dysfunction. To offset this metabolic imbalance, H. armigera mobilized triglycerides and amino acids as alternative energy sources. Reinforcing antioxidant defenses, membrane remodeling, and activating apoptotic and neuromodulatory pathways plausibly aided in restoring cellular homeostasis. Collectively, these findings reveal a tightly coordinated physiological tug of war in H. armigera, where the detrimental effects of rCanPI-7-induced oxidative and nutritional stress were countered through compensatory metabolic, structural, and signaling adjustments. This study provides the first lipidomic insight into this pest species, offering a deeper understanding of its biochemical resilience and potential metabolic vulnerabilities for targeted biopesticide strategies.